Consumer online dispute resolution (ODR) - Jeretina, Urša (Central European Public Administration Review, 2018)
Online Dispute Resolution (ODR) could be the first important step towards adjusting the public Administration to the requirements of the digital era by introducing new e-disputes. In this context, this article examines the significance of the emergence of consumer ODR systems in EU as a new mechanism for resolving disputes, online ones included. It takes a theoretical research approach to evaluate the nature and scope of ODR development in the emerging field of e-governance and combine it with a comparative data analysis to identify the core positive and negative challenges in the use of ODR. Some EU member states have already adopted ODR as a tool for digital e-government and others are still in the period of its implementation. ODR has already proved effective resolution for at least some disputes (e.g. cross-border disputes), but unfortunately has not yet reached its full potential. The lack of relevant ODR case law is another issue that contributes to only gradual usage of ODR systems and their efficiency. Key findings are formulated as a list of challenges that EU has to face for efficient use of ODR and it as an important part within innovative European e-governance in the future.
Keywords: digitalna doba; elektronsko poslovanje; e-upravljanje; inovativno upravljanje; ODS; potrošniki; reševanje sporov; varstvo potrošnikov